Interdependensi dalam Belenggu Diplomasi - M. Elfan Kaukab (Resolusi: Jurnal Sosial Politik, 2020)
To mark the existence of power is one of the interests of why the border wall was built, which was carried out even by earlier nations. The basic purpose of why the wall fence was built is to maintain sovereignty over neglected areas, protect wealth and population, and protect cultural values ​​from the influence of other state systems that are owned by immigrants. 26 walls have been built as political borders between national borders, whether established by the military regime or democracy. Wall construction is an issue that can not only be seen from a political aspect but also from the perspective of diplomacy, migration, and architecture.